2022
DOI: 10.1128/mbio.02076-22
|View full text |Cite
|
Sign up to set email alerts
|

Optical O 2 Sensors Also Respond to Redox Active Molecules Commonly Secreted by Bacteria

Abstract: When they are closely packed, as in biofilms, colonies, and soils, microbes can consume O 2 faster than it diffuses. As such, O 2 concentrations in natural environments can vary greatly over time and space, even on the micrometer scale.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, there was no difference in reduction rates on different sugars at pH 7.5 and in some cases reduction rates appeared higher on pyruvate than on the other sugars, an observation that has been made in other experimental contexts ( 29 ). Direct measurements of oxygen in our experiments are not possible given current technologies ( 49 ) as any disturbance in shaking would alter oxygen tensions precluding an accurate measurement of the oxygen concentrations experienced by cells. Succinate and pyruvate are both organic acids, and despite medium buffering (which cannot be increased due to toxicity concerns), it is also possible that shifts toward more alkaline pH during growth on these substrates further decrease PCA reduction ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no difference in reduction rates on different sugars at pH 7.5 and in some cases reduction rates appeared higher on pyruvate than on the other sugars, an observation that has been made in other experimental contexts ( 29 ). Direct measurements of oxygen in our experiments are not possible given current technologies ( 49 ) as any disturbance in shaking would alter oxygen tensions precluding an accurate measurement of the oxygen concentrations experienced by cells. Succinate and pyruvate are both organic acids, and despite medium buffering (which cannot be increased due to toxicity concerns), it is also possible that shifts toward more alkaline pH during growth on these substrates further decrease PCA reduction ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used nanosensors 24 , electrochemical profiling [25][26][27] and Pcco2-mediated biosensing 25,28 to study the oxygen gradients and redox profile of P. aeruginosa biofilms. While these studies have provided robust insights into the chemical microenvironment within the bulk mass of pseudomonad biofilms, the void structures of E. coli transport channels presented a priority for this study which would inform if the local conditions might impact on future channel-exploiting treatments.…”
Section: Discussionmentioning
confidence: 99%
“…recently documented the common pitfalls in oxygen nanosensing applications in biofilms, where the constituent cells can produce quenching molecules that may impact on the reliability of optical oxygen quantifications 24 . We therefore provided a spatial overview of the relative change in nanosensor intensity as a function of oxygen depletion along biofilm transport channels and supplemented this ratiometric data with high resolution electrochemical sensing experiments.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli BL21 (DE3) were used as the model suspension culture system, where it was recently reported that secreted molecules from E. coli do not affect the behavior of porphyrin-based oxygen nanosensors. 40 Different concentrations of bacteria were cultured over a 15 h period with the oxygen levels monitored continuously. As the number of cells in suspension increased, the added effects of respiration and oxygen depletion also increased, as shown in Figure 5A.…”
Section: Acs Sensorsmentioning
confidence: 99%